Linguagem, tecnologia e ação humana: um diálogo entre a pragmática Wittgensteiniana da linguagem e a filosofia da tecnologia reformacional de tradição neerlandesa. - Andrade, Danyllo Gomes Figueredo de (2023)
This dissertation seeks to carry out an interdisciplinary analysis of the relationship between language, technology, and human action. To fulfill this task, we draw upon, on the one hand, the theoretical framework of wittgensteinian pragmatics, particularly the concepts of meaning as use, language games, and form of life, and on the other hand, the conceptual developments on technology from Dutch reformational philosophy. The aim of this analysis is to obtain a broader understanding of human action based on the understanding and relationship between language and technology. It is concluded that there is a convergence between the concepts of meaning as use and use as meaning in technological artifacts, as well as a relationship between the idea of language games and the grammar of the artifact. The concept of form of life is expanded with the concepts of structure, context, and direction derived from reformational philosophy.